2004
DOI: 10.1111/j.1399-0039.2004.00263.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of killer cell immunoglobulin‐like receptor gene diversity III. KIR2DL3

Abstract: The allelic variation of one of the chromosome 19 KIR genes, KIR2DL3, has been investigated using a polymerase chain reaction sequence-specific oligonucleotide probe-based methodology. The procedure has been applied to a healthy Northern Irish control group in order to establish phenotype and genotype frequencies in this Caucasian population. In addition, cell line DNA and Centre d'Etude du Humaine (CEPH) families, both from the 13th International Histocompatibility Workshop have been investigated, establishin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 16 publications
1
19
1
Order By: Relevance
“…In order to determine specifically which allelic variant of these genes predominates in the two groups of patients, we carried out an oligotyping analysis of KIR2DL2 and KIR2DL3 , as previously described [35], [36]. In relation to KIR2DL3 , we found that the KIR2DL3*001 allele was most common in SVR while KIR2DL2*001 was more frequent in NSVR.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In order to determine specifically which allelic variant of these genes predominates in the two groups of patients, we carried out an oligotyping analysis of KIR2DL2 and KIR2DL3 , as previously described [35], [36]. In relation to KIR2DL3 , we found that the KIR2DL3*001 allele was most common in SVR while KIR2DL2*001 was more frequent in NSVR.…”
Section: Discussionmentioning
confidence: 98%
“…Based on the results of KIR genotyping, patients with KIR2DL2 and/or with KIR2DL3 genes were genotyped as described elsewhere [35], [36] to identify different alleles. 146 NSVR and 103 SVR patients were randomly selected for this study.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous report on 77 families in Northern Ireland (plus an additional 27 families added more recently) we examined KIR genes and alleles, making it possible to ascertain if an individual had one or two copies of the gene, although it was necessary to make some assumptions 32 . Gene content was first ascertained 23 and those genes present were allele typed 33–39 . Of the 418 haplotypes of the parents of the 104 families (haplotype information was derived from three parents in one family), there were 122 different haplotypes, taking into account both genes and alleles.…”
Section: Haplotypesmentioning
confidence: 99%
“…36 KIR gene and allele typing PCR-SSOP for KIR genes was performed as previously described. 37,38 For KIR allele subtyping, PCR amplifications and SSOP hybridizations were performed as previously described: KIR2DL3, 39 45 Upgraded allele typing systems were devised for KIR2DS4 (to distinguish *003 from *007), KIR2DL4 (to discriminate between 9A and 10A alleles) and to resolve KIR3DL2 subtyping of genotypes containing ambiguous combinations of certain alleles. 46 Only one allele of KIR2DS1 and KIR2DS5 was present in the Irish.…”
Section: Subjects and Dna Isolationmentioning
confidence: 99%